Purchasing behavior of UiTM student ( Sabah branch ) on bun / Ronahlizah Mutang - Mutang, Ronahlizah (2007)
My research is about purchasing behavior of UiTM student (Sabah branch) on Bun. In this research, I want to know the problem that faced by Koperasi of UiTM when selling Bun. The problems that I want to investigate are student satisfaction in terms of price, packaging, quality of Bun and many more. The purpose of my study, is to identify the level of student satisfaction on purchasing Bun, to identify the objection faced by UiTM's Koperasi and to know the strategy that used by the UiTM's to attract students to buy Bun. When conducting this research, I made a questionnaire which consist of 16 questions, after that I distribute the questionnaire to 90 respondents. My respondents are the student in UiTM (Sabah branch) which are the customer of UiTM's Koperasi. I also made an interview which 30 respondents are interviewed by me. After collected the questionnaire and interview, I have analyzed it with the SPSS version 12.0 software to reduce errors in analyzing the questionnaire. As the conclusion, I hope that my findings will be useful for students for better decision when but bun in UiTM's Koperasi. And this is my recommendation to UiTM's Koperasi where increase the level of satisfaction on price, packaging, and quality of the Bun in order to attract more student to buy Bun. Finally, I provide a final report which consists of my findings. This is the complete report which determines all of my problems, experience, limitations and so on.